Antique coloring of the burning process to increase the variety of finishing of export commodity pottery products - Timbul Raharjo; Yulriawan Dafri; Lutse Lambert Morin; Yulyta Kodrat Prasetyaningsih; Wahyu Tri Atmojo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Coloring plays an important role as an artistic consideration in pottery products for the export market. Burning technique coloring is one of the innovative finishing techniques that have an antique impression. The purpose of this paper is to experiment with the finishing of the burnt technique and its application to the surface of the pottery body to make it look antique or ancient. This is an effort to increase the variety of finishing on the products of the Kasongan Yogyakarta pottery industry. Kasongan is the largest pottery industry in Indonesia. Kasongan Yogyakarta pottery has become an international trade commodity. This paper uses a qualitative descriptive method with an explanation of the flow of the experimentation process for the combustion technique of coloring on Kasongan pottery. The experiment resulted in four findings of the burning technique, namely (1) antique green, (2) antique blue, (3) antique brown, and (4) antique earth color. The experimental results were applied to 8 pottery in the form of statues and decorative vases. It is hoped that it can add variations to the coloring of pottery products and increase sales of Kasongan pottery products.